Principles of sport administration - Leonard, Richard (Morgantown, WV : Fitness Information Technology, 2013)
Athletic program administrators have a tremendous influence on the success of their organizations. They must construct viable program plans; oversee budgeting, marketing, and fundraising efforts; and effectively manage employees. These concepts and many more are covered in Principles of Sport Administration, and indispensible guide for any aspiring athletic program administrator.
Section I: Management concepts for athletic program administrators -- Section II: Internal program administration -- Section III: Marketing concepts for athletic program administrators -- Section IV: External program administration and other business applications
Includes bibliographical references and index.
Keywords: Fund raising; Public relations; Sports administration; Management concepts; Sports -- Economic aspects